Impairment of patient-reported outcomes among patients with non-alcoholic fatty liver disease: a registry-based study - YILMAZ, YUSUF; KEKLİKKIRAN, ÇAĞLAYAN (My University, 2022)
Background Patients with non-alcoholic fatty liver disease (NAFLD) and more advanced fibrosis tend to have more impairment in their health-related quality of life and other patient-reported outcomes (PROs). Aim To assess the association of PROs with select non-invasive tests (NITs) for fibrosis including FAST, Agile 3+ and Agile 4 scores Methods We enrolled patients with an established diagnosis of NAFLD who were seen in a tertiary care clinic into the NAFLD/NASH Registry. The FAST, Agile 3+ and Agile 4 scores were calculated using liver stiffness measurements by transient elastography and laboratory parameters. PROs were assessed using FACIT-F, CLDQ-NASH and WPAI instruments (total of 17 domain and summary scores). Results There were 1509 patients with NAFLD (mean age: 49 +/- 11 years, 50% men, 41% employed, 30% advanced fibrosis and 20% cirrhosis). The mean FAST, Agile 3+ and Agile 4 scores were 0.39 +/- 0.26, 0.35 +/- 0.31 and 0.12 +/- 0.23, respectively. Subjects with lower FAST, Agile 3+ and Agile 4 scores had the highest scores in select domains of FACIT-F, CLDQ-NASH and WPAI (p < 0.05 in comparison to subjects with elevated or high-risk NIT scores). Correlations with continuous NITs were significantly negative for Emotional and Functional well-being (FACIT-F), Activity/energy, Systemic symptoms, Worry and total scores (CLDQ-NASH), and Activity of WPAI (p < 0.05); the strongest was for Worry (CLDQ-NASH) with FAST (R = -0.17, p < 0.0001). The PRO scores of patients with NAFLD were lower than those of matched patients with chronic hepatitis B (p < 0.05 for 9/17 domain and summary scores). Conclusion Patients with NAFLD and high FAST, Agile 3+ or Agile 4 scores experience impairment of health-related quality of life.
Keywords: Tıp; Temel Eczacılık Bilimleri; Dahili Tıp Bilimleri; İç Hastalıkları; Gastroenteroloji-(Hepatoloji); Eczacılık; Yaşam Bilimleri; Sağlık Bilimleri; Temel Bilimler; Medicine; Basic Pharmaceutics Sciences; Internal Medicine Sciences; Internal Diseases; Gastroenterology and Hepatology; Pharmacology and Therapeutics; Life Sciences; Health Sciences; Natural Sciences; GASTROENTEROLOJİ VE HEPATOLOJİ; Klinik Tıp; Klinik Tıp (MED); FARMAKOLOJİ VE ECZACILIK; Farmakoloji ve Toksikoloji; Yaşam Bilimleri (LIFE); GASTROENTEROLOGY & HEPATOLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); PHARMACOLOGY & PHARMACY; PHARMACOLOGY & TOXICOLOGY; Life Sciences (LIFE); Farmakoloji; Farmakoloji, Toksikoloji ve Eczacılık (çeşitli); Genel Farmakoloji, Toksikoloji ve Eczacılık; Farmakoloji (tıbbi); Hepatoloji; Gastroenteroloji; İlaç Rehberleri; Pharmacy; Pharmacology; Pharmacology, Toxicology and Pharmaceutics (miscellaneous); General Pharmacology, Toxicology and Pharmaceutics; Pharmacology (medical); Hepatology; Gastroenterology; Drug Guides